2016
DOI: 10.1080/14767058.2016.1174995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaginal cleansing on postoperative factors in elective caesarean sections: a prospective, randomised controlled trial

Abstract: The preoperative vaginal cleansing with povidone iodine could reduce the postoperative pain, analgesic need and infection parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Except for their median age, that the three groups were similar in terms of their socio-demographic characteristics (height, weight, parity, educational attainment and income status) is important for the reliability of the study. The results of the present study are consistent with those of Göymen et al 's study [19]. In the present study, there were no statistical differences between the groups regarding the duration of surgery, preoperative Hgb, Hct and WBC values, levels of PCT at the postoperative 24 th hour, and VAS score for pain at the postoperative 6 th hour.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Except for their median age, that the three groups were similar in terms of their socio-demographic characteristics (height, weight, parity, educational attainment and income status) is important for the reliability of the study. The results of the present study are consistent with those of Göymen et al 's study [19]. In the present study, there were no statistical differences between the groups regarding the duration of surgery, preoperative Hgb, Hct and WBC values, levels of PCT at the postoperative 24 th hour, and VAS score for pain at the postoperative 6 th hour.…”
Section: Discussionsupporting
confidence: 93%
“…However, the number of studies investigating the effect of preoperative vaginal cleansing on postoperative maternal morbidity in primiparous women undergoing elective caesarean section is limited. Similar to the present study, in their study, Göymen et al, found that in primiparous women undergoing elective caesarean section, pre-operative vaginal cleansing with povidone iodine and chlorhexidine reduced postoperative pain and that CRP values at the 24 th hour were lower [19]. Although, vaginal cleansing before caesarean section is more effective in decreasing postoperative infection morbidity in women with premature ruptured membranes whose labor started, this study also showed that vaginal cleansing performed with normal saline solution or povidone iodine solution just before birth in primiparous women undergoing elective caesarean section statistically significantly decreased postoperative pain, fever and CRP levels, which is a biochemical marker of infection, compared to the women in the control group.…”
Section: Marmara Medical Journalsupporting
confidence: 90%
See 1 more Smart Citation
“…One study noted improved pain scores until 7 days postoperatively [135] while the other did not report any pain reduction [36]. Pre‐operative vaginal cleansing resulted in minor but statistically significant reductions in postoperative pain scores [137].…”
Section: Resultsmentioning
confidence: 99%
“…to evaluate the effect of vaginal cleansing with povidone iodine versus benzalkonium chloride before CS on postpartum infectious morbidities. Povidone iodine group showed statistically significant reduction in both postoperative pain and CRP levels 24 hours after CS, when compared to the control group [15]. In our intervention there was statistically significant difference (p value=0.005) between the intervention group (received vaginal clindamycin) and the control group (received nothing) as regard white blood cells (WBC) count 24 hours after CS and.…”
Section: Göymen Et Al Performed An Interventionmentioning
confidence: 57%